Habitus dan Modal Sosial dalam Praktik Perjodohan di Madura: Dampaknya terhadap Agensi Perempuan - Salsabila, Salma Laili; Kirana, Novrinda Gatri; Arizhatifa, Fatmah; Ramadina, Mutia Naura; Ridwan, Ahmad; Handoyo, Pambudi (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
Arranged marriages and early marriages remain embedded in the social life of some Madurese communities, even though modern developments have increasingly given women more space to determine their own life choices. This tradition is rooted in the belief that marriage serves as a means to maintain the family’s good name and preserve long-standing social relationships built across generations. This study aims to reveal how family habitus and social capital sustain the continuation of arranged marriage practices, and how these dynamics influence the extent of women’s control over decisions related to their marriage. Using a qualitative approach, this study conducted in-depth interviews with three categories of women: those who fully comply with tradition, those who accept arranged marriages as a consequence of maintaining family harmony, and those who have begun to critique the tradition because they feel entitled to choose their own partners. The findings show that habitus functions as a guiding framework for families in evaluating women's propriety and morality through engagement practices prior to courtship, while social capital is mobilized to ensure that the chosen match comes from a family deemed compatible in terms of status, religious networks, and reputation. When habitus and social capital operate strongly, women’s agency tends to weaken; conversely, greater access to education and broader insight opens opportunities for women to negotiate or even reject arranged marriages. This study concludes that arranged marriage is not merely a cultural tradition, but also a family strategy to maintain their position within the social structure. Throughout this process, women continuously negotiate the space they have in making decisions about their own lives.